Case of the Very Rare Gallbladder Paraganglioma - Shreya, Shukla; Kashikar, Ritu; Shraddha, Sinhasan R.; Shrinivas, Desai (Indian Journal of Radiology and Imaging, 2021)
Gallbladder paraganglioma is a very rare condition, and only a few cases have been reported in the literature. Herein, we present and discuss the clinical and radiological findings of a 72-year-old woman who complained of heaviness, pain, and on and off watery discharge from the left ear for 1 year and reduced hearing in both ears. She was thoroughly investigated radiologically where multiple paragangliomas were found with the discovery of the very rare gallbladder paraganglioma. There is a need to realize the importance of thorough radiological evaluation in cases of head and neck paraganglioma to look for more such lesions in the body for early identification of patients with familial paraganglioma syndromes. With this practice, gene mutation carriers can be identified early in the course of their disease and brought to surgical attention before their disease becomes extensive and potentially life-threatening.
Keywords: CECT head and neck tumors; DOTATATE PET/CT; gallbladder paraganglioma; glomus tumors; multiple paragangliomas